2019
DOI: 10.1177/0165551519837174
|View full text |Cite
|
Sign up to set email alerts
|

Visual analysis of information world maps: An exploration of four methods

Abstract: Information researchers increasingly use participatory, arts-based methods to better understand the social contexts of individuals and populations. However, it remains rare to engage in qualitative analysis of the resulting visual artefacts. This article explores approaches to analysing visual media generated through a specific arts-based method, information world mapping (IWM), an interdisciplinary draw-and-talk technique that elicits data about individuals’ social information worlds. Here, we test four appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 51 publications
(68 reference statements)
1
21
0
Order By: Relevance
“…Situational analysis (Clarke, 2005) illuminated the discursive power underlying these themes. Like Greyson et al (2019), we found it valuable first to analyze interview transcripts to have an underlying context for interpreting the maps.…”
Section: Discussionmentioning
confidence: 99%
“…Situational analysis (Clarke, 2005) illuminated the discursive power underlying these themes. Like Greyson et al (2019), we found it valuable first to analyze interview transcripts to have an underlying context for interpreting the maps.…”
Section: Discussionmentioning
confidence: 99%
“…Situational analysis and qualitative content analysis were used to examine the data as suggested by D. Greyson et al () for analyzing IWM data. The unit of analysis is individual participants.…”
Section: Methodsmentioning
confidence: 99%
“…drawings or timelines, which use images "to drive interview discussion" (Hicks & Lloyd, 2018, 231), "to represent mental models" or "to solicit people's conceptualization" (Zhang, 2008(Zhang, , 1331; -the information horizon interview (Sonnenwald et al, 2001) -"the first and currently best-established visual method for the study of information behaviour" (Hartel, 2017); -photo-elicitation methods, e.g. the photo-diaries and photovoice (Hartel & Tomson, 2011;Hicks & Lloyd, 2018); -IWM -the information world mapping (Greyson et al, 2019); -and even the information mapping board game (Le Louvier & Innocenti, 2019). Imagery may be analyzed by various qualitative techniques: compositional interpretation, conceptual analysis, grounded theory approach, pictorial metaphor analysis, thematic analysis, and visual discourse analysis -situational analysis (Greyson et al, 2019;Hartel, 2014b;Hartel & Savolainen, 2016;Hicks, 2018).…”
Section: Visual Data In the Information Behavior Researchmentioning
confidence: 99%
“…the photo-diaries and photovoice (Hartel & Tomson, 2011;Hicks & Lloyd, 2018); -IWM -the information world mapping (Greyson et al, 2019); -and even the information mapping board game (Le Louvier & Innocenti, 2019). Imagery may be analyzed by various qualitative techniques: compositional interpretation, conceptual analysis, grounded theory approach, pictorial metaphor analysis, thematic analysis, and visual discourse analysis -situational analysis (Greyson et al, 2019;Hartel, 2014b;Hartel & Savolainen, 2016;Hicks, 2018).…”
Section: Visual Data In the Information Behavior Researchmentioning
confidence: 99%